(untitled) (Eurasian Research Bulletin, 2025)
This article studies the theoretical and practical aspects of the effective use of tax incentives. Proposals and recommendations for possible reforms in tax policy in 2026 were developed. The study analyzed the impact of incentives on the efficiency of business entities, the investment climate, and the development of competition. On this basis, the need to simplify the system of incentives, target groups, and strengthen their monitoring mechanism was justified. The proposed measures are aimed at making tax policy more effective, stabilizing budget revenues, and improving the business environment